ANALYSIS OF RESERVOIR DISTRIBUTION FROM TALANGAKAR FORMATION, JIRAK FIELD, SOUTH SUMATRA BASIN - Stephani, Grace
Jirak Field is one of Pertamina’s old fields that have been producing oil and gas since 1929. In 1940, Jirak reached its primary peak production of 8886 bopd. Although Jirak has been proven as a prolific oil and gas reservoir, the oil recovery factor steel remain of 18%. First zone is one of the producing reservoir zones in Jirak. It is an early Miocene sandstone and member of Talangakar Formation. The production history and performance of First zone show a pattern distribution in north and south area. This is challenging in term of field development potential. Based on biostratigraphy analysis result from JRK-237, core and petrography analyses from JRK-228, it can be determined that First zone consist of sublitharenite with very fine to fine in grain size and show an abundant burrows at the upper part. The sedimentary structure give a characteristic of intertidal environement, associated with delta front. Routine core analysis of JRK-228 combined with seismik interpretation of Jirak 2D seismik line SB-02 and basement configuration map shows that First zone’s sandstone are building blocks of fluvial-dominated delta where sediment source from north east to south west. Sandstone of First zone can be divided into 3 (three) fasies: distributary channel, distributary mouthbar and shale. Production data analysis were done by creating an oil cummulative production bubble map of First zone from 97 producer wells since 1929 until now. Purpose of this analysis is to recognize the compartmentalization in Jirak field. The interpretation made before this study stated that a northeast-southwest faults acting as sealing faults therefore Jirak have compartmentalized into two compartments. By this study, it can be concluded that compartmentalization in. Jirak was not caused by stuctural but stratigraphy. There were shale barriers in the middle of the field that seperate north area from south area of Jirak. The result of this study shows a reservoir distribution and compartmentalization in Jirak. Hopefully this study can be used as a guideline in planing and implementing field development scenarios, specifically for waterflooding project in Jirak.